Construction of RC shear wall / Nur Adha Radhiah Ab Llah - Radhiah Ab Llah, Nur Adha (Universiti Teknologi Mara, Perak, 2014)
This practical training report is about the process and method that involved for the construction of the RC shear wall . I have made this practical training report based on my experience for 4 months on the site. This practical training report have some parts, it is divided with the company background and my case study background. Based on the my experience and observation at the site ,the construction of shear wall is complicated to be construct. There are many methods and process to construct a shear wall. In this report, it contained the summary of the construction of the RC shear wall, the material, equipment, components and machinery that use for the construction of the shear wall. Besides, in this practical training report also, I have included with the method on how to construct the RC shear wall. Hence, it is started from the BRC of the shear wall, the installation of the steel formwork , the ready mix concrete and dismantling of formwork. When the construction process of the RC shear wall being hold, there have several problems arise and I can identified the problems. This practical training report has been include with the several comments and recommendation from my opinion that can solve the problems that arise. In conclusion, from this practical training report that I has done, I can explain with detailed to all the reader about the construction of the RC shear wall.